2015
DOI: 10.1140/epje/i2015-15102-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell protein dynamics reproduce universal fluctuations in cell populations

Abstract: Protein variability in single cells has been studied extensively in populations, but little is known about temporal protein fluctuations in a single cell over extended times. We present here traces of protein copy number measured in individual bacteria over multiple generations and investigate their statistical properties, comparing them to previously measured population snapshots. We find that temporal fluctuations in individual cells exhibit the same properties as those previously observed in populations. Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(96 citation statements)
references
References 36 publications
6
90
0
Order By: Relevance
“…In addition to the work presented here Brenner et al (13,14) have shown other ordered processes (growth and division) can generate universal statistical distributions for protein copy numbers in populations (13) and individual microorganisms (14). The ordered recursive nature of growth and division has shared mathematical roots and structure with the ordered mechanical arrest process presented.…”
Section: Discussionsupporting
confidence: 52%
“…In addition to the work presented here Brenner et al (13,14) have shown other ordered processes (growth and division) can generate universal statistical distributions for protein copy numbers in populations (13) and individual microorganisms (14). The ordered recursive nature of growth and division has shared mathematical roots and structure with the ordered mechanical arrest process presented.…”
Section: Discussionsupporting
confidence: 52%
“…• Protein number increases as e kit during the i th generation, where the exponential growth rate k i fluctuates with i [8].…”
Section: Model Without Feedbackmentioning
confidence: 99%
“…2a. The data points were collected from six individual trajectories normalized to unit average (data from [8]). In agreement with Eq.…”
Section: Comparison With Datamentioning
confidence: 99%
See 1 more Smart Citation
“…These include bacteria [7][8][9][10], budding yeast [10][11][12][13][14] and mammalian cells [10,15]. Moreover, the mRNA and protein numbers are on average proportional to the cell volume throughout the cell cycle [16][17][18][19][20]. Therefore, the homeostasis of mRNA concentration and protein concentration is maintained in an exponentially growing cell volume.…”
mentioning
confidence: 99%